Helicopter In-flight Resuscitation with Freeze-dried Plasma of a Patient with a High-velocity Gunshot Wound to the Neck in Afghanistan – A Case Report. Issue 5 (1st September 2015) - Gellerfors, Mikael; Linde, Joacim; Gryth, Dan
Abstract: Massive hemorrhage with coagulopathy is one of the leading causes of preventable death in the battlefield. The development of freeze-dried plasma (FDP) allows for early treatment with coagulation-optimizing resuscitation fluid in the prehospital setting. This report describes the first prehospital use of FDP in a patient with carotid artery injury due to a high-velocity gunshot wound (HVGSW) to the neck. It also describes in-flight constitution and administration of FDP in a Medevac Helicopter. Early administration of FDP may contribute to hemodynamic stabilization and reduction in trauma-induced coagulopathy and acidosis. However, large-scale studies are needed to define the prehospital use of FDP and other blood products. M Gellerfors, J Linde, D Gryth .Helicopter in-flight resuscitation with freeze-dried plasma of a patient with a high-velocity gunshot wound to the neck in Afghanistan – a case report .Prehosp Disaster Med .2015 ;30 (5 ):509 –511 .